2009
DOI: 10.1017/s0022149x09990277
|View full text |Cite
|
Sign up to set email alerts
|

The helminth community of the wood mouseApodemus sylvaticusin a Mediterranean ecosystem in regeneration ten years after a wildfire

Abstract: This study was carried out 10 years after a wildfire in the Spanish Serra Calderona Natural Park, following a previous analysis comprising the first 5 years after the fire. Its primary aim was to elucidate the impact of this perturbation on the population biology of the wood mouse Apodemus sylvaticus, and the repercussions on its helminth community in this regenerating Mediterranean ecosystem. Second, confirmation of the ability of the parasites to tolerate environmental stressors and the effects on their tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 29 publications
4
18
4
Order By: Relevance
“…Thus, this nematode might play an important role in helminth community stability, explaining the high prevalence of infection detected. Other studies have reported a low prevalence or even the absence of this nematode in perturbed areas, supporting the association between the presence of H. polygyrus and population stability (Fuentes et al, 2007a(Fuentes et al, , 2010. Moreover, the oxyurid S. stroma had the highest abundance, which agrees with other similar studies reporting a high helminth burden of Syphacia species (Behnke et al, 1999;Fuentes et al, 2003Fuentes et al, , 2004aTorres et al, 2003;Eira et al, 2006;Milazzo et al, 2010) and with the ecology of this nematode, directly transmitted host to host.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, this nematode might play an important role in helminth community stability, explaining the high prevalence of infection detected. Other studies have reported a low prevalence or even the absence of this nematode in perturbed areas, supporting the association between the presence of H. polygyrus and population stability (Fuentes et al, 2007a(Fuentes et al, , 2010. Moreover, the oxyurid S. stroma had the highest abundance, which agrees with other similar studies reporting a high helminth burden of Syphacia species (Behnke et al, 1999;Fuentes et al, 2003Fuentes et al, , 2004aTorres et al, 2003;Eira et al, 2006;Milazzo et al, 2010) and with the ecology of this nematode, directly transmitted host to host.…”
Section: Discussionsupporting
confidence: 81%
“…Fourteen helminth species were found in this study, a number equal to or higher than those reported in other studies (Portolés et al, 2000;Torres et al, 2003;Fuentes et al, 2004a, b;Torre et al, 2013) but lower than those reported by Fuentes et al (2007aFuentes et al ( , 2010 for various enclaves of the Iberian Peninsula.…”
Section: Discussioncontrasting
confidence: 51%
“…Tetrathyridia of Mesocestoides sp. have been reported previously as parasites of rodents and insectivores in mainland Spain as well as in Spanish islands, but with no detection of aberrancies such as those reported in the present study (Feliu et al 1997;Mas-Coma et al 1998;Fuentes et al 2000Fuentes et al , 2004Fuentes et al , 2005Fuentes et al , 2007Fuentes et al , 2009Torres et al 2003;Sainz-Elipe et al 2007). It is likely that Mesocestoides is widespread among A. sylvaticus throughout the Iberian Peninsula, but tetrathyridia were not found in a recent detailed survey of this host in the Coimbra District of Portugal (Eira et al 2006).…”
Section: Discussioncontrasting
confidence: 70%
“…This ecosystem suffered a devastating wildfire at the end of the summer of 1992 (Fuentes et al 2007(Fuentes et al , 2010.…”
Section: Methodsmentioning
confidence: 99%
“…This rodent is the normal host of numerous species of capillariin nematodes; two of which, namely Aonchotheca annulosa and Eucoleus bacillatus, were found as component species of A. sylvaticus in Serra Calderona Natural Park, a Mediterranean ecosystem in post-fire regeneration where the helminth community of the wood mouse has been widely studied (Fuentes et al 2000(Fuentes et al , 2007(Fuentes et al , 2010.…”
Section: Introductionmentioning
confidence: 99%